2015
DOI: 10.1186/s12862-015-0323-3
|View full text |Cite
|
Sign up to set email alerts
|

Opposite environmental and genetic influences on body size in North American Drosophila pseudoobscura

Abstract: BackgroundPopulations of a species often differ in key traits. However, it is rarely known whether these differences are associated with genetic variation and evolved differences between populations, or are instead simply a plastic response to environmental differences experienced by the populations. Here we examine the interplay of plasticity and direct genetic control by investigating temperature-size relationships in populations of Drosophila pseudoobscura from North America. We used 27 isolines from three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…The results of their study suggest that the mutations affect the body size of the males and the females reversibly. Patterns of chromosome inversions also favor the body size dimorphism as reported by Taylor et al 80 in Drosophila pseudoobscura. In addition to body size, there is another most important sexual dimorphic character, the sex comb of Drosophila.…”
Section: Genetic Basis For Sexual Dimorphismsupporting
confidence: 57%
“…The results of their study suggest that the mutations affect the body size of the males and the females reversibly. Patterns of chromosome inversions also favor the body size dimorphism as reported by Taylor et al 80 in Drosophila pseudoobscura. In addition to body size, there is another most important sexual dimorphic character, the sex comb of Drosophila.…”
Section: Genetic Basis For Sexual Dimorphismsupporting
confidence: 57%
“…Regarding body size, Conover et al (2009) noted seven examples of countergradient variation and two examples of the cogradient pattern, both directional patterns in Drosophila. Additional information is provided by Taylor et al (2015) in a study designed to examine the covariance pattern between temperature-size rule and Bergmann's rule in another Drosophila species. The authors observed countergradient variation in body size.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila , selection on body size is correlated with temperature (Taylor et al 2015), and survival is affected by climate change (Bozinovic et al 2016). Machado et al (2016) performed a longitudinal study of Drosophila collected at differing latitudes during a two year time span and compared physiological traits of two different species: D. melanogaster and D. simulans .…”
mentioning
confidence: 99%